PERSEPSI MAHASISWA PADA EARNING MANAGEMENT “STUDI KASUS MAHASISWA SEMESTER TUJUH UNIVERSITAS SURABAYA, TAHUN 2017” - Yenny Sugiarti; Jenifer (Akuntansi dan Teknologi Informasi, 2018)
This study aims to determine students' perceptions of earningss management practices including student’s perception about real earnings management, student’s perception regarding accrual earnings management. In addition, this study also observe whether or not student perceive difference between real earnings management and accrual earnings management. This study used questionnaires and then the data obtained will be processed using descriptive statistics of mean and mode. The results of questionnaire data that have been processed will be deepened with Focus Group Discussion (FGD). The results of this study indicate that there is no difference in student perceptions for real earnings management practices and accrual earnings management.